2012
DOI: 10.4103/0971-3026.111476
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and significance of incidentally detected focal colonic uptake on FDG PET/CT

Abstract: Background:Incidental colonic uptake of 18F-flurodeoxyglucose (FDG) is not an infrequent finding encountered during whole body positron emission tomography (PET) imaging. Almost all studies on this topic are in Western populations, which have a markedly different epidemiological profile for colorectal premalignant and malignant conditions as compared to that of the Indian subcontinent.Aim:The purpose of this study was to assess the etiology of incidentally detected focal FDG uptake in the colon by comparing it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
4
5
0
Order By: Relevance
“…concluded that malignancy could not be ruled out based on SUVmax alone because the differences of SUVmax between the premalignant adenomatous polyps and the malignant lesions was not significant. [ 10 13 ] This is consistent with our observation of the SUVmax in our study. A comparison between benign and malignant SUVmax values by Roh et al .…”
Section: Discussionsupporting
confidence: 93%
“…concluded that malignancy could not be ruled out based on SUVmax alone because the differences of SUVmax between the premalignant adenomatous polyps and the malignant lesions was not significant. [ 10 13 ] This is consistent with our observation of the SUVmax in our study. A comparison between benign and malignant SUVmax values by Roh et al .…”
Section: Discussionsupporting
confidence: 93%
“…No significant difference in SUVmax was observed the two groups with focal or diffuse incidental GIT uptake, and no significant difference in SUVmax, SUVpeak, SUV50 and SUV41 was observed between the four diagnosis groups, confirming previously published data [ 13 , 14 , 18 – 20 , 23 , 35 , 36 ]. In our study, the mean SUVmax of diffuse FDG uptake was slightly higher than the mean SUVmax of focal FDG uptake, although diffuse FDG uptake was generally associated with a benign diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Colorectal cancer was detected incidentally in 3 of a series of 230 (1.3 %) patients, which is higher than the rate observed in various FDG PET/CT cancer screening studies, such as that reported by Chen et al with a colorectal cancer incidence of 0.19 % (6/3210), Terauchi et al with an incidence of 0.96 % (28/2911), and Purandare et al with an incidence of 0.055 % (5/9000) [ 33 – 35 ] probably related to potential common risk factors between colon cancer and lung cancer in our series.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, focal FDG uptake, which is observed in 0.4 % to 16.3 % of patients undergoing PET/CT examinations, is usually associated with the discovery of malignant and pre-malignant lesions in almost 68 % of patients 6 . Consequently, false-positive findings have been reported in 9.3 % to 63 % of these cases 9 10 11 12 13 14 15 16 17 18 19 20 21 22 . Although the mechanisms of FDG uptake in the large bowel are unclear, false-positive uptake is thought to be the consequence of the physiological accumulation of FDG 23 24 .…”
Section: Introductionmentioning
confidence: 99%